Entrepreneurial leadership, learning organization and organizational culture relationship: A systematic literature review - Robson Mekonnin Shiferaw; Zerihun Ayenew Birbirsa; Shimels Zewdie Werke (Journal of Innovation and Entrepreneurship, 2023)
The purpose of this study is to examine the relations between organizational culture, learning organizations, and entrepreneurial leadership. The study concentrated on how organizational culture, learning organizations, and entrepreneurial leadership are measured in the literature. The study used a systematic literature review methodology analysis that was published in reputable and peer-reviewed English research journals to look at how organizational culture, learning organizations, and entrepreneurial leadership are related to one another. The study used content analysis on 27 peer-reviewed journal articles that were discovered in various journals examined in the databases, which was based on a systematic examination of the literature. This study offers a comprehensive view of entrepreneurial leadership that has been linked to learning organizations and organizations in various enterprises and nations. The study looked at research approaches, sample sizes, data gathering tools, implications, and limits from the body of literature. The study is also one of the first of its kind to review the research on the connection between entrepreneurial leadership, learning organizations, and organizational culture. The outcomes of this study help the scientific community underline the connection between entrepreneurial leadership, learning organizations, and organizational culture for upcoming policy makers.
Keywords: 650; Entrepreneurial leadership; Learning organization; Organizational culture